An unusual case of congenital cytomegalovirus infection-related retinopathy. Issue 1 (December 2016) - Tagami, Mizuki; Honda, Shigeru; Morioka, Ichiro; Iijima, Kazumoto; Yamada, Hideto; Nakamura, Makoto
Abstract Background Cytomegalovirus (CMV) is the most common congenital infection, and chorioretinitis is the most common ophthalmic manifestation of congenital CMV infection. We experienced a unique case of CMV retinopathy showing unusual retinal vessels. Case presentation An infant boy weighing 1860 g was born at 36 weeks. He was diagnosed with severe symptomatic congenital CMV infection, which was confirmed by positive CMV-DNA in urine and whole blood, and he was referred to our ophthalmology department on his first day of life. Ophthalmoscopic examination and fluorescein angiography revealed no chorioretinitis but major retinal vascular occlusions and arterio-venous anastomosis associated with CMV detection in the aqueous humor. These findings regressed within a week after treatment with systemic gancyclovir administration. Conclusions To our knowledge, there are no reports of these ocular issues associated with congenital CMV infection. These findings may be useful for the early and rapid diagnosis of congenital CMV infection.